Government Spending and Indonesia's Multidimensional Poverty 2018-2020 - Ramadhani, Azzahra Alifa; Ridwan, Endrizal (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to analyze the effect of government spending on multidimensional poverty in Indonesia in 2018-2020. The government expenditure used is government expenditure for housing functions, public facilities and social assistance expenditure. This research uses a quantitative approach and Tobit panel regression techniques as well as secondary data for 2018-2020. The research results show that government spending, both government spending for public facilities housing functions and social assistance spending, has a positive and significant effect on multidimensional poverty in Indonesia. This research recommends to the Government that in making expenditure policies it is necessary to examine more broadly the impact on multidimensional poverty. Furthermore, the Government needs to evaluate and review the effectiveness of policies that have been implemented to reduce poverty, especially multidimensional poverty, which can be done through budget decomposition based on programs, so that the effect of spending on poverty can be seen in more detail.